Tension hydrothorax: emergency decompression of a pleural cause of cardiac tamponade (2018)
Introduction A tension hydrothorax is defined as a massive pleural effusion presenting with hemodynamic abnormalities secondary to mediastinal compression. In these patients pleural volume increases intrathoracic pressure to the point of compromising diastolic filling and cardiac output simulating a cardiac tamponade physiology. This is an uncommon yet potentially fatal medical emergency that if left untreated may progress to cardiac arrest. Early detection and rapid intervention of these patients prevents cardiorespiratory collapse. Case presentation We present a two-case report of patients presenting with malignant tension hydrothoraxes decompressed with ultrasound-guided thoracentesis and tube thoracostomy in the ED. Conclusion Although these life-saving decompressive interventions appear simple, not having proper training is an independent factor for chest tube and thoracentesis complications. Courses and simulation training can benefit physicians to minimize potential complications when managing emergency conditions such as tension hydrothoraxes which continue to be a medical challenge. Whether thoracentesis or thoracostomy is superior in managing this condition remains in debate and a clinical dilemma.